Early life high-fat diet exposure evokes normal weight obesity - Maejima, Yuko (Nutr Metab (Lond), 2020)
Obesity is becoming one of the most severe global health problems. However, risk of developing normal weight obesity, where an individual has a high percentage of body fat despite a normal body mass index, is gaining attention since such individuals also develop systemic inflammation and metabolic dysregulation. In this study, juvenile (3-week-old) and adult (8-week-old) rats were fed a high fat diet (HFD) for 9 weeks and compared them with normal chow diet (NCD) fed rats. The HFD fed adult group showed increase in energy intake, body weight (BW), total fat, visceral fat and subcutaneous fat compared with an age-matched NCD group. In addition, the percentage of muscle mass to BW in the adult HFD group was significantly lower compared with the NCD group. When HFD feeding was started from the juvenile stage, there were almost no differences in energy intake and BW between the HFD and NCD groups. However, the juvenile HFD group showed a 1.7-fold increase in total fat, visceral fat and subcutaneous fat compared with their age-matched NCD group. The percentage of muscle mass to BW was significantly lower in the juvenile HFD group compared with the NCD group. In addition, increased plasma insulin levels and decreased insulin sensitivity was observed only in juvenile HFD group, but not in adult HFD group. These results suggest that HFD feeding in growth period induces insulin resistance and normal weight obesity. Here we show a method for generating a normal weight obesity model, as well as raising the alarm for developing normal weight obesity when children are exposed to high-fat meals.